A Multipurpose Collapsible Scaffold for Flat and Irregular Surfaces - Rosalie Grace S. De La Cruz (Civil Engineering Journal, 2023)
The construction industry heavily relies on scaffolding to facilitate work at elevated heights. This study presents a new and innovative design for a collapsible, multifunctional scaffold that is suitable for both flat and irregular surfaces. The design of the scaffold was evaluated using a Likert scale survey, which revealed high acceptability across all evaluated categories. The scaffold was fabricated using a combination of steel and aluminum materials and designed using computer-aided design CAD software. The fabrication process, portability, performance, and safety of a prototype scaffold were thoroughly assessed. The evaluation methodology employed a Likert-scale questionnaire and a descriptive research approach. A total of 30 engineers, architects, and construction laborers participated in the evaluation, assessing four essential aspects of the scaffold. The results indicated a consistently high level of acceptability, with weighted mean scores ranging from 4.69 to 4.94 out of a maximum score of 5.0 in all categories. The design parameters of the scaffold, such as the footing mechanism and working platform design, were determined based on industry standards and the intended usage of the scaffold. However, this study did not include a sensitivity analysis to explore the impact of different parameter values on the scaffold's performance. This study introduces a collapsible, multifunctional scaffold that effectively addresses the limitations of traditional scaffolds by offering enhanced portability, safety, and adaptability to flat and irregular surfaces. The widespread adoption of this scaffold design is expected to have significant implications for the construction industry, improving productivity and safety in construction projects. Doi: 10.28991/CEJ-SP2023-09-09 Full Text: PDF